Gereja Orang Miskin: Studi Teologi Sistematika terhadap Dalil ke-43 Martin Luther dan Relevansinya bagi Teologi Sosial HKBP dalam Konteks Kemiskinan Kontemporer - Ericxon Ebenezer Nainggolan; Pintor Marihot Sitanggang (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2026)
The Church continues to face significant challenges in responding to poverty, social inequality, and the marginalization of vulnerable communities. This article examines the theological meaning of poverty from a Christian systematic theology perspective by analyzing Martin Luther’s Forty-Third Thesis and contextualizing its relevance within the theological documents of the Huria Kristen Batak Protestan (HKBP). Employing a qualitative theological approach through literature analysis, this study explores biblical perspectives on poverty, Luther’s theological critique of Christian attitudes toward wealth and poverty, and HKBP’s understanding of the Church’s social responsibility. The findings indicate that Luther’s Forty-Third Thesis emphasizes that Christian faith requires active solidarity, compassion, and responsibility toward the poor rather than merely offering religious sympathy. Furthermore, the study reveals that HKBP’s theological documents reflect a contextual understanding of the Church as an institution called to participate in social transformation through advocacy, empowerment, and service to marginalized groups. This article contributes to theological studies by integrating Luther’s Reformation theology with the contextual social theology of HKBP, demonstrating that the concept of the “Church of the Poor” is not only a theological ideal but also a practical ecclesiological commitment in addressing contemporary poverty.